2018
DOI: 10.1002/14651858.cd004328.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid for patients with nasal haemorrhage (epistaxis)

Abstract: Analysis 1.3. Comparison 1 Tranexamic acid versus placebo plus usual care or usual care alone, Outcome 3 Severity of rebleeding: proportion of patients requiring blood transfusion within 10 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 31 publications
1
40
0
3
Order By: Relevance
“… 11 It has also been studied for the treatment of epistaxis. 10 , 12 TXA is quickly becoming a standard of care in the treatment of adult trauma patients, with studies ongoing in pediatric trauma patients. 13 A few of these studies have shown a slightly higher risk for postoperative seizures; however, the majority of studies show that TXA has minimal side effects.…”
Section: Discussionmentioning
confidence: 99%
“… 11 It has also been studied for the treatment of epistaxis. 10 , 12 TXA is quickly becoming a standard of care in the treatment of adult trauma patients, with studies ongoing in pediatric trauma patients. 13 A few of these studies have shown a slightly higher risk for postoperative seizures; however, the majority of studies show that TXA has minimal side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In another prospective study, FloSeal ® effectively controlled posterior bleeds in 8 of 10 patients whose initial packing failed [61]. Surgicel ® and Gelfoam ® are common conformable hemostatic materials and have been described in reviews or small case series as useful in nasal bleeding refractory to cautery [62]. These materials can be trimmed to an appropriate size and then applied directly to the bleeding source.…”
Section: Epistaxismentioning
confidence: 99%
“…The Cochrane Review discussed here included randomized controlled trials comparing tranexamic acid (TXA) in any formulation (e.g., delivered orally, intravenously, or topically) with usual care versus usual care with placebo, usual care with any other hemostatic agent, or usual care alone . The primary outcome was the proportion of patients with rebleeding within 10 days and significant adverse events (i.e., seizures, thromboembolic events).…”
Section: Narrativementioning
confidence: 99%